2023
DOI: 10.1021/acs.orglett.3c02666
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Visible Light Triggered Formation of trans-Cyclohexene for the Contra-thermodynamic Protection of Alcohols

Pritha Das,
Megan DeSpain,
Avery Ethridge
et al.

Abstract: We report herein a method for the contra-thermodynamic protection and thermodynamic deprotection of alcohols in which all reagents are returned to their original state. This is accomplished by the use of visible light photochemical energy to drive the formation of a highly strained trans-(Z)-cyclohexene. At STP the product ethers contain more potential energy than the starting materials and, thus, can be catalytically returned to the starting materials, effectively realizing a protection–deprotection scheme pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Trans- cyclohexenes were observed as transient photochemical species . Recently, Weaver et al , demonstrated the use of visible light to activate the cis -/ trans -photoisomerization of a cyclohexene and showed that the resulting trans- cycloalkene could then readily undergo addition reactions with alcohols and urethanes. Trans- cycloheptenes and trans- cyclooctenes can be prepared and can drive strain-promoted reactions, , and even larger cycloalkenes rings have less twisted double bonds …”
mentioning
confidence: 99%
“…Trans- cyclohexenes were observed as transient photochemical species . Recently, Weaver et al , demonstrated the use of visible light to activate the cis -/ trans -photoisomerization of a cyclohexene and showed that the resulting trans- cycloalkene could then readily undergo addition reactions with alcohols and urethanes. Trans- cycloheptenes and trans- cyclooctenes can be prepared and can drive strain-promoted reactions, , and even larger cycloalkenes rings have less twisted double bonds …”
mentioning
confidence: 99%